2023
DOI: 10.7862/rm.2023.5
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Finite Element Method to Simulate the Friction Phenomenon in a Strip Drawing Test

Abstract: Friction is an undesirable phenomenon in the flange area of the drawpiece in sheet metal forming processes, causing a deterioration in surface finish and a decrease in the formability limits of the sheet metal. The aim of this work is numerical analysis using the finite element method of the strip drawing test with two rounded countersamples. This test simulates friction conditions in the flange area of the drawpiece. The results of the experimental research on the influence of surface roughness on the value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The min-max function (Equation ( 5)) was used to normalise the data, which allowed the values of the input parameters and the output parameter to be transformed into the range [0, 1]. In fact, normalisation modifies the value of the data, but it achieves this while maintaining information about the distance between each point: N = X − x min x max − x min (5) where X is the value of the normalised parameter and x min and x max are minimum and maximum values of the normalised parameter, respectively. The entire training set contained 120 sets of input parameters and the corresponding value of the coefficient of friction.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The min-max function (Equation ( 5)) was used to normalise the data, which allowed the values of the input parameters and the output parameter to be transformed into the range [0, 1]. In fact, normalisation modifies the value of the data, but it achieves this while maintaining information about the distance between each point: N = X − x min x max − x min (5) where X is the value of the normalised parameter and x min and x max are minimum and maximum values of the normalised parameter, respectively. The entire training set contained 120 sets of input parameters and the corresponding value of the coefficient of friction.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…This method of plastic working is fast and does not cause production waste, which is inherent in machining processes [4]. The properties of the finished product, such as the surface quality, are mainly influenced by the friction and lubrication conditions [5]. During the deformation process, friction causes a change in the surface topography and material flow character of the deformed workpiece and a deterioration in the surface quality of the product [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the friction and wear of materials, the following types of tests and tribometers may be used: (a) strip drawing test with flat [ 19 , 20 ] and (b) rounded [ 21 ] (c) countersamples, (d) bending-under-tension test [ 22 , 23 ], (e) draw-bead test [ 24 , 25 ], and (f) ball-on-disc [ 26 ], (g) block-on-disc [ 27 ], (h) pin-on-ring [ 28 ], and (i) pin-on-disc tribometers [ 29 , 30 ]. Most of the studies, the results of which can be found in the literature, indicate the susceptibility of aluminium sheets to galling and intensification of the flattening mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The model of the surface layer of the tool and workpiece is characterised by several properties that determine the occurrence and participation of individual wear mechanisms (Figure 3). Owing to the subjection of different areas of the tool to nominal pressures and friction conditions, many tests were developed to simulate friction conditions only in selected places of the formed sheet, i.e., strip drawing test [30], a bending under tension test [31] and a draw bead test [32,33].…”
Section: Introductionmentioning
confidence: 99%